In vivo quantification of embryonic and placental growth during gestation in mice using micro-ultrasound - Qu Dawei; Slevin John C; Mu Junwu; McCormick Sarah; Adamson S Lee (BMC, 2008)
Abstract Background Non-invasive micro-ultrasound was evaluated as a method to quantify intrauterine growth phenotypes in mice. Improved methods are required to accelerate research using genetically-altered mice to investigate the interactive roles of genes and environments on embryonic and placental growth. We determined (1) feasible age ranges for measuring specific variables, (2) normative growth curves, (3) accuracy of ultrasound measurements in comparison with light microscopy, and (4) weight prediction equations using regression analysis for CD-1 mice and evaluated their accuracy when applied to other mouse strains. Methods We used 30-40 MHz ultrasound to quantify embryonic and placental morphometry in isoflurane-anesthetized pregnant CD-1 mice from embryonic day 7.5 (E7.5) to E18.5 (full-term), and for C57Bl/6J, B6CBAF1, and hIGFBP1 pregnant transgenic mice at E17.5. Results Gestational sac dimension provided the earliest measure of conceptus size. Sac dimension derived using regression analysis increased from 0.84 mm at E7.5 to 6.44 mm at E11.5 when it was discontinued. The earliest measurement of embryo size was crown-rump length (CRL) which increased from 1.88 mm at E8.5 to 16.22 mm at E16.5 after which it exceeded the field of view. From E10.5 to E18.5 (full term), progressive increases were observed in embryonic biparietal diameter (BPD) (0.79 mm to 7.55 mm at E18.5), abdominal circumference (AC) (4.91 mm to 26.56 mm), and eye lens diameter (0.20 mm to 0.93 mm). Ossified femur length was measureable from E15.5 (1.06 mm) and increased linearly to 2.23 mm at E18.5. In contrast, placental diameter (PD) and placental thickness (PT) increased from E10.5 to E14.5 then remained constant to term in accord with placental weight. Ultrasound and light microscopy measurements agreed with no significant bias and a discrepancy of less than 25%. Regression equations predicting gestational age from individual variables, and embryonic weight (BW) from CRL, BPD, and AC were obtained. The prediction equation BW = -0.757 + 0.0453 (CRL) + 0.0334 (AC) derived from CD-1 data predicted embryonic weights at E17.5 in three other strains of mice with a mean discrepancy of less than 16%. Conclusion Micro-ultrasound provides a feasible tool for in vivo morphometric quantification of embryonic and placental growth parameters in mice and for estimation of embryonic gestational age and/or body weight in utero.